A STUDY ON THE QUALITY OF NATURAL FLAVORING POWDER PROCESSED FROM SHRIMP WASTE - Richal Susilo; Suparmi '; Edison ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This research aimed to determine the quality and the application of natural flavoring powder processed from shrimp waste. This study used a non factorial completely randomized design (CRD). The treatment was addition of wheat flour, consisted of 3 level, namely: without wheat flour added (R0), added with wheat flour 1:1 (R1), and added with wheat flour 1:2 (R2) and repeated in 3 replications. The result showed that the increasing wheat flour added at different ratio was affected to the quality of the flavoring powder based on the value of taste and odor. Flavoring powder of shrimp contained 17 amino acid, consisted of 9 essential amino acids and 8 non essential amino acids. The highest content of essential amino acid was leusin amounted of 0,362% and the highest content of non essential amino acid was glutamic acid amounted of 0,913%. Odor threshold value on the powder flavor of shrimp to taste was 8% at the ratio of 1: 8. Meanwhile, odor threshold value on the aroma of shrimp flavor powders were 12% in the ratio of 1: 9. The greater the ratio of dilution was formed, the lower shrimp taste and aroma in the shrimp flavor powder, even reduced to undetectable.Keywords: Natural flavoring, shrimp waste, amino acids